2014
DOI: 10.1186/2193-1801-3-408
|View full text |Cite
|
Sign up to set email alerts
|

Third degree formic acid chemical burn in the treatment of a hand wart: a case report and review of the literature

Abstract: ObjectiveCutaneous warts are very common and a large variety of topical treatments and drugs can be employed to cure these skin injuries that can arise on any part of the body. But are these products really safe?MethodWe performed a case description and PubMed literature review using key words “wart,” “chemical burn,” and “formic acid.” All articles in English and French were selected.ResultsThis is the first report of a chemical burn by formic acid in the treatment of warts. Numerous topical treatments for cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Epithelization occurred 7-10 and 10-14 days post-treatment in warts with a small and large crust, respectively (Figs. [2][3][4][5][6][7][8]. Nail dystrophy and severe post-treatment scarring were not observed in any of the patients.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Epithelization occurred 7-10 and 10-14 days post-treatment in warts with a small and large crust, respectively (Figs. [2][3][4][5][6][7][8]. Nail dystrophy and severe post-treatment scarring were not observed in any of the patients.…”
Section: Resultsmentioning
confidence: 61%
“…With such commonly used treatment methods as cryotherapy, salicylic acid, lactic acid, monochloroacetic acid, and formic acid, control of the precise depth of treatment depth is not possible. [1][2][3] As such, aggressive treatment of hand warts can easily lead to unintended tissue damage, resulting in aesthetic and functional deformity 1,4 that requires complex reconstruction, including skin grafts and flaps. Consequently, clinicians treating hand warts often favor conservative treatments in an effort to avoid damaging normal tissue surrounding the wart, which commonly results in incomplete and superficial treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The high success rate of wart treatment has been mentioned after topical puncture with 85% formic acid in a period of 1 to 3 months [6,7]. Tippanawar et al have also reported that 82% of patients treated with 80% formic acid intralesionally achieved complete disappearance of warts after 10 applications [4].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its efficacy, the use of formic acid is an inexpensive option with no equipment requirements. In addition, the risk of posttreatment scarring and nail dystrophy is low, and patients can return to their occupations immediately; no local anesthesia is required, which makes it well tolerated by children [4,[6][7][8]. As in all therapies, treatment with formic acid, a chemical acid, poses some adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…This healed spontaneously; however, a sensory deficit in the course of the underlying ulnar collateral nerve was noted. 17 Tong et al reported a case of inappropriate use of anti-wart treatment containing formic acid in an adult resulting in a full-thickness injury over the little finger proximal interphalangeal joint (PIPJ) and secondary cellulitis requiring extensive debridement and reconstruction. In this case the injury resulted in significant functional impairment due to PIP and distal interphalangeal joint (DIPJ) stiffness.…”
Section: Discussionmentioning
confidence: 99%